UMBILICAL CORD BLOOD HEMATOLOGY IN RELATION WITH MATERNAL ANEMIA: A PRELIMINARY STUDY - Debbarma, Rumi; Pankaj, Pankaj; Devi, M. Anita (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The aim of this study was to observe any umbilical cord blood hematological changes in relation to maternal anemia. Methods: We conducted a cross-sectional study on 220 neonates and their mothers from August 1, 2015, to July 31, 2016, in collaboration with the Department of Obstetrics and Gynaecology, Regional Institute of Medical Sciences, Imphal, India. Immediately after vaginal delivery of baby, umbilical cord was clamped and blood was collected in EDTA vials and analyzed using automated hematoanalyzer. Results: Neonates of non-anemic mothers had significantly higher level of hemoglobin concentration than neonates of anemic mothers. Total leukocyte count (TLC) was slightly higher in neonates of non-anemic mothers as compared to neonates of anemic mothers. Platelet count was slightly higher in neonates of anemic mothers as compared to non-anemic mothers, but platelet crit, mean platelet volume, and platelet cell distribution width were slightly higher in neonates of non-anemic mothers than neonates anemic mothers. Conclusions: It was a preliminary study. A similar type of the study must be conducted in future to comprehend the effect of various other factors affecting delivery such as maternal anemia, diet, and environment on blood parameters of newborns.